The Gloria of Abrera an analysis of the editorial cartoons of Jess Abrera in the PDI from 2004 to 2005 - Acibar, Gretel Lagonde 1985- (Quezon City College of Mass Communication, University of the Philippines Diliman, 2006)
"This is a qualitative study on the editorial cartoons of Jess Abrera published in the Philippine Daily Inquirer portraying President Gloria Macapagal - Arroyo from 2004 to 2005. It aimed to investigate the influence of these cartoons in shaping public opinion through the direct and indirect messages that they give. The instruments used to investigate the effectiveness of cartoons in conveying opinions were interviews. FGDs and content analysis of randomly selected cartoons published in PDI from 2004 to 2005. The results showed that the editorial cartoons, as part of the editorial page, convey an opinion of the artist but do not necessarily affect the perception of the readers toward an issue involving PGMA. It was concluded that the editorial cartoons merely reinforced the pre-existing ideas on issues concerning the Arroyo administration."
Vita.
Thesis (A.B. Journalism)--University of the Philippines Diliman